Pengaruh Kecepatan Putar Pengadukan Adonan terhadap Sifat Fisik Roti (Effect of Dough Mixing Speed on Bread Physical Characteristic): Effect of Dough Mixing Speed on Bread Physical Characteristic - Asih Priyati; Sirajuddin H. Abdullah; Guyup Mahardhian Dwi Putra (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2016)
This research aimed to study effect of dough mixing speed on bread physical characteristic. Dough mixing is an important process on bread production. At this process, the cohesive elastic characteristic will occur from gluten that attach water molecule. Method used in this research was experimental approach using Completely Randomized Design with variation of mixer speed and determined correlation between physical characteristic of the expansion bread after fermentation and after baked in the oven, bread mass, bread pore, and bread water content. Mixer speed variation of 100, 150, and 200 rpm using three replications had been conducted. Result showed that mixing process using higher speed produced bigger bread mass, larger bread pore, and higher water content.